GLITCH ART SEBAGAI REFLEKSI MEMORI MANUSIA YANG RAPUH: SEBUAH PENCIPTAAN KARYA SENI - Hadiyan Yusuf Kuntoro (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
AbstractIn the era that has entered the digital revolution, academic publication articles on the creation of digital-based fine art are still not widely found compared to the creation of conventional fine art. One area of the digital art creation that has a limited number of academic publication articles is the creation of glitch art. In this article, the creation of glitch art is presented along with the explanation of the definition of glitch art, the methods of creation, the technical embodiment, and the concrete artworks. The creation method follows the nine stages of creation: preparation, concentration, incubation, ideation, insight, verification, planning, production, and validation. Glitch art as the visual idea is used as an object to express the creative idea about the fragility of human memory. The technique used in the artwork creation is data bending. By utilizing the digital visual data as the metaphor for memory, the distortion process is carried out to create artistic expressions in the artworks. The application used in the distortion process is Audacity, an open-source digital audio editor application software. The purpose of this article is to enrich the variety of academic publication articles on the topic of fine art creation which are still dominated by the conventional fine art creation articles.Keywords: digital art, glitch art, memory, data bending, contemporary art.AbstrakDi era revolusi digital, paparan dalam ranah publikasi ilmiah mengenai penciptaan seni rupa berbasis digital masih belum banyak ditemukan dibandingkan dengan penciptaan seni rupa konvensional. Salah satu cabang dari penciptaan seni rupa digital yang paparan publikasi ilmiahnya masih terbatas adalah tentang penciptaan karya glitch art. Dalam artikel ini, penciptaan karya glitch art dipaparkan dengan penjelasan perihal definisi glitch art, metode penciptaan, teknis perwujudan, dan wujud konkret karya. Metode penciptaan karya mengikuti sembilan tahapan penciptaan, yaitu preparation, concentration, incubation, ideation, insight, verification, planning, production, dan validation. Glitch art sebagai gagasan visual dijadikan wadah untuk mengekspresikan gagasan kreatif kerapuhan memori manusia. Teknik yang digunakan dalam penciptaan karya adalah data bending. Dengan memanfaatkan data visual digital sebagai metafora dari memori, proses distorsi dilakukan guna menciptakan ungkapan-ungkapan yang artistik dalam karya. Aplikasi yang digunakan dalam proses distorsi adalah Audacity, sebuah aplikasi edit audio digital berbasis open-source. Artikel penciptaan ini bertujuan untuk memperkaya ragam artikel penciptaan pada publikasi ilmiah yang selama ini masih didominasi oleh artikel penciptaan seni rupa konvensional.Kata Kunci: seni digital, glitch art, memori, data bending, seni kontemporer Author:Hadiyan Yusuf Kuntoro : Institut Seni Indonesia Yogyakarta ReferencesAbdullah, A. M. (2021). Paradoks Bunuh Diri sebagai Ide dalam Penciptaan Karya Seni Grafis. Journal of Contemporary Indonesian Art, 7(1). 50-56. https://doi.org/10.24821/jocia.v7i1.5276Adam, S. (2018). Seni Lukis sebagai Refleksi Ketidakberdayaan dan Keterpinggiran Cokek. Mudra Jurnal Seni Budaya, 33(1), 1-8. https://doi.org/10.31091/mudra.v33i1.323Adityatama, R. (2020). Apresiasi pada Film Menumbuhkan Rasa Empati sebagai Ide Penciptaan Karya Seni Grafis. Journal of Contemporary Indonesian Art, 6(2), 121-129. https://doi.org/10.24821/jocia.v6i2.5113Asa, F. O., Ahdi, S., & Elpatsa, A. (2021). Fenomena Korupsi: Tikus sebagai Inspirasi Lukis. Gorga: Jurnal Seni Rupa, 10(2), 508-514. https://doi.org/10.24114/gr.v10i2.28059Ayuningtari, A. W. K. (2022). Youth Cyberbullying sebagai Tema Penciptaan Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 11(2), 521-528. https://doi.org/10.24114/gr.v11i2.39164Botella, M., Zenasni, F., & Lubart, T. (2011). A Dynamic and Ecological Approach to the Artistic Creative Process of Arts Students: An Empirical Contribution. Empirical Studies of the Arts, 29(1), 17-38. https://doi.org/10.2190/EM.29.1.bBullot, N. J., Seeley, W. P., & Davies, S. (2017). Art and Science: A Philosophical Sketch of Their Historical Complexity and Codependence. The Journal of Aesthetics and Art Criticism, 75(4), 453-463. https://doi.org/10.1111/jaac.12398Cahyono, E. (2020). Kehidupan Fauna sebagai Ide Penciptaan Karya Seni Patung. Journal of Contemporary Indonesian Art, 6(1), 28-37. https://doi.org/10.24821/jocia.v6i1.4722Crowther, P. (2008). Ontology and Aesthetics of Digital Art. The Journal of Aesthetics and Art Criticism, 66(2), 161-170. https://doi.org/10.1111/j.1540-6245.2008.00296.xden Heijer, E. (2013). Evolving Glitch Art. Dalam P. Machado, J. McDermott, A. Carballal (Eds.), Evolutionary and Biologically Inspired Music, Sound, Art and Design (pp. 109-120). Springer. https://doi.org/10.1007/978-3-642-36955-1_10Dickerson, B. C., & Eichenbaum, H. (2010). The Episodic Memory System: Neurocircuitry and Disorders. Neuropsychopharmacology, 35(1), 86-104. https://doi.org/10.1038/npp.2009.126Faruq, U., & Hamzah, A. (2022). Living Qur™an dalam Karya Seni Lukis. Journal of Contemporary Indonesian Art, 8(2). 122-131.Fritz, D. (2016). International Networks of Early Digital Arts. Dalam C. Paul (Ed.), A Companion to Digital Art (pp. 46-68). John Wiley & Sons Inc. https://doi.org/10.1002/9781118475249.ch2Galanter, P. (2016). Generative Art Theory. Dalam C. Paul (Ed.), A Companion to Digital Art (pp. 146-180). John Wiley & Sons Inc. https://doi.org/10.1002/9781118475249.ch5Goodfellow, P. (2022). Channelling the Unknown: Noise in Art Ecosystems. Arts, 11(2), 39. https://doi.org/10.3390/arts11020039Hidayatulloh, T. I. I. (2022). Visualisasi Ibu dan Ayah dalam Karya Patung Assembling. Gorga: Jurnal Seni Rupa, 11(2), 505-512. https://doi.org/10.24114/gr.v11i2.39923Kane, C. L. (2016). GIFs that Glitch: Eyeball Aesthetics for the Attention Economy. Communication Design, 4(1-2), 41-62. http://doi.org/10.1080/20557132.2016.1275478Kemper, J. (2023). Glitch, the Post-digital Aesthetic of Failure and Twenty-First-Century Media. European Journal of Cultural Studies, 26(1), 47-63. https://doi.org/10.1177/13675494211060537Kusrini. (2016). Fotografi Jalanan: Membingkai Kota dalam Cerita. Journal of Urban Society™s Arts, 3(2), 102-109. https://doi.org/10.24821/jousa.v3i2.1482Liffa, M., & Sihite, O. (2023). Coffee Shop sebagai Ide Penciptaan Seni Lukis Kaca dengan Teknik Reverse. Gorga: Jurnal Seni Rupa, 12(1), 70-78. https://doi.org/10.24114/gr.v12i1.40961Lilipaly, M. R. H., & Wiyono. (2022). Visualisasi Garis Tangan Biografi Tokoh sebagai Ide Penciptaan Karya Seni Lukis. Journal of Contemporary Indonesian Art, 8(1), 39-48.Menkman, R. (2011). The Glitch Moment(um). Institute of Network Cultures. https://networkcultures.org/_uploads/NN%234_RosaMenkman.pdfMigotuwio, N. (2020). Aspek Komunikasi Visual dan Estetika pada Karya Desain Grafis Bergaya Glitch Art. Journal of Contemporary Indonesian Art, 6(1), 48-64. https://doi.org/10.24821/jocia.v6i1.3901PeÃ±a, E., Dobson, T. M., & JuÃ¡rez, O. (2017). Pixualization: Glitch Art and Data Visualization. InfoDesign - Revista Brasileira De Design Da InformaÃ§Ã£o (InfoDesign - Brazilian Journal of Information Design), 14(1), 89-105. https://doi.org/10.51358/id.v14i1.502Prastyo, I. D., & Zarkasi, M. S. (2019). Wujud Rasa Syukur sebagai Keluarga Petani dalam Visual Karya Seni Grafis. Brikolase: Jurnal Kajian Teori, Praktik, dan Wacana Seni Budaya Rupa, 11(1), 52-69. https://doi.org/10.33153/brikolase.v11i1.2675Puyt, R. W., Lie, F. B., & Wilderom, C. P. M. (2023). The Origins of SWOT Analysis. Long Range Planning, 56(3), 102304. https://doi.org/10.1016/j.lrp.2023.102304Qeis, M. I., & Azizi, M. F. (2017). Eksplorasi Visual Psychedelic Experience Melalui Ilustrasi Berbasis Seni Psychedelic. Jurnal Desain, 4(3), 275-281. http://dx.doi.org/10.30998/jurnaldesain.v4i03.1608Read, S., Comas-Herrera, A., & Grundy, E. (2020). Social Isolation and Memory Decline in Later-life. The Journal of Gerontology: Series B, 75(2), 367-376. https://doi.org/10.1093/geronb/gbz152Shaw, D. B. (2020). The Aesthetics of Retrieval: Beautiful Data, Glitch Art, and Popular Culture. Anthropocenes - Human, Inhuman, Posthuman, 1(1), 13. https://doi.org/10.16997/ahip.15Sufajar, H. B. (2020). Barang Sehari-hari sebagai Metafor dalam Penciptaan Seni Patung. Journal of Contemporary Indonesian Art, 6(2), 101-106. https://doi.org/10.24821/jocia.v6i2.5098Wiggins, R. H., Davidson, H. C., Harnsberger, H. R., Lauman, J. R., & Goede, P. A. (2001). Image File Formats: Past, Present, and Future. RadioGraphics, 21(3), 789-798. https://doi.org/10.1148/radiographics.21.3.g01ma25789